Resilience of Archipelagic Regions to Hydrometeorological Disasters: A Multidimensional Approach to Infrastructural, Social, and Economic Aspects - Amelia Masza; Mulia Pamadi; Gilbert Trio Junanda (Journal of Civil Engineering and Planning (JCEP), 2026)
Background: Hydrometeorological disasters are the most dominant type of disaster in Indonesia and have a significant impact on archipelagic regions due to their geographical characteristics, limited connectivity, and high dependence on weather and sea conditions. These conditions make archipelagic regions vulnerable to floods, high waves, storms, coastal abrasion, and sea level rise, which impact infrastructure, social, and economic aspects. Objective: This study aims to assess the resilience of archipelagic regions to hydrometeorological disasters through a multidimensional approach that includes infrastructure, social, and economic aspects. Method: The study used the Systematic Literature Review (SLR) method through the process of identifying, screening, evaluating, and synthesizing articles from Google Scholar and ScienceDirect databases using Publish or Perish software. From the initial search results of 973 articles, 5 articles were obtained that met the inclusion criteria and were relevant to the research topic. Results: The results of the study indicate that the resilience of archipelagic regions is influenced by the relationship between infrastructure, social, and economic aspects. Coastal infrastructure and transportation play an important role in maintaining regional connectivity, while social cohesion, institutional capacity, and early warning systems support preparedness and post-disaster recovery. Furthermore, the tourism, fisheries, and logistics sectors are the economic sectors most vulnerable to hydrometeorological disturbances. Conclusion: Building resilience in archipelagic regions requires a multidimensional approach through strengthening adaptive infrastructure, increasing community social capacity, and developing economic systems that are resilient to disasters and climate change.